Application of artificial intelligence in nursing practice: a qualitative study of Jordanian nurses’ perspectives - Wesam Taher Almagharbeh; Hazem AbdulKareem Alfanash; Khaldoon Aied Alnawafleh; Amal Ali Alasmari; Faris Abdelkarim Alsaraireh; Mutaz M. Dreidi; Abdulqadir J. Nashwan (BMC Nursing)
Abstract Background Artificial Intelligence (AI) is increasingly applied in healthcare to boost productivity, reduce administrative workloads, and improve patient outcomes. In nursing, AI offers both opportunities and challenges. This study explores nurses’ perspectives on implementing AI in nursing practice within the context of Jordan, focusing on the perceived benefits and concerns related to its integration. Method A qualitative research approach was employed, involving semi-structured interviews with 25 nurses and 3 focus group discussions, each consisting of 7–8 participants. The data collected was coded and analyzed using thematic analysis to identify recurring patterns and key themes in the nurses’ views on AI. Results Three major themes emerged from the analysis: (1) AI as an efficiency tool – Nurses recognized AI’s ability to reduce administrative burdens and improve patient monitoring in real-time. (2) Ethical and practical concerns – Nurses raised issues regarding patient privacy, data security, and the fear that AI might replace human decision-making in care. (3) Lack of preparedness and training – There was a consensus on nurses’ inadequate training in AI tools, limiting their ability to integrate AI into their practice fully. Conclusion While AI is seen as a valuable tool to enhance nursing productivity, several challenges still need to be addressed, particularly regarding ethical concerns and insufficient training. To ensure AI complements nursing without compromising the human element, healthcare institutions must address these issues by implementing comprehensive training programs and establishing clear ethical guidelines.